Experimental and numerical fatigue life study of cracked AL plates reinforced by glass/epoxy composite patches in different stress ratios. Issue 6 (1st July 2021) - Hosseini, K.; Safarabadi, M.; Ganjiani, M.; Mohammadi, E.; Hosseini, A.
Abstract: In this study, the fatigue behavior of composite reinforced cracked aluminum 1050 plates is investigated experimentally and numerically. The tests are conducted in four different stress ratios between 0 and 1. At first step, plates with similar cracks and geometries have been prepared. Then the glass/epoxy patches have been attached to the cracked plates using Araldite 2015 adhesive. Fatigue load has been applied to three cases of samples including non-patch, one-side patch and two-side patch, where in all stress ratios the maximum force is considered constant. A three-dimensional finite element analysis is developed in ABAQUS. A good correlation between finite element results and the corresponding experimental data was observed. The results illustrated that two-side patch sample has the most fatigue strength. It is found that for two-side patch samples, fatigue life has been increased approximately 2000% and 4800% in the stress ratios R = 0 and 0.5, respectively in comparison with the non-patched samples. Communicated by Krzysztof Kamil Żur.